Incorporação da voz do cliente nas etapas iniciais do desenvolvimento de sistemas produto-serviço (PSS) - Mazo, Sara Zuluaga (2012)
Product-Service Systems (PSS) are designed to satisfy customers’ needs through a service that includes: products, support networks and infrastructure. Although many authors around the world have studied PSS, there are very few methods for service design based on the customers’ quality perception. The purpose of this work is to provide a tool that incorporates the customers’ voice at the early stages of the development of Product-Service Systems and, with this, to provide a reference model and propose future research opportunities. To meet the main objective, literature review was conducted, including the definition of PSS, the different types of PSS, the benefits and barriers of its implementation, different models for designing PSS and the support tools that incorporate the customer´s voice in the Product Development Process (PDP) and that could possibly assist the designing process of PSS. The tool that best addressed the requirements of the PSS design was the Quality Function Deployment (QFD). QFD is an effective tool for translating the customers’ voice into engineering parameters, as it is able to introduce the quality topic into the development of PSS. The starting point of the present work was to improve existing studies of QFD utilization in PSS development. Then the model is application is illustrated with a laundry business case. The model that supports PSS development has two main barriers, which are associated with the relationship matrix qualitative evaluation and with the possible complexity in working with large amounts of quality characteristics.